PENGARUH PENGAWASAN TERHADAP KINERJA KARYAWAN PADA INDUSTRI JASA PERDAGANGAN DAN KOPERASI DAN USAHA KECIL MENENGAH KABUPATEN PASER - Sri Kurniati Idha; Achmad Syahruddin; Amir Hamzah (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
The research was conducted at the Department of Industry, Trade and Cooperatives & Small and Medium Enterprises, Paser Regency. The purpose of this study was to determine the effect of Supervision consisting of Internal Supervision (X1), External Supervision (X2), Preventive Supervision (X3), and Repressive Supervision (X4) on Employee Performance (Y) at the Office of Industry, Trade and Cooperatives & Small and Medium Enterprises of Paser Regency. The population in this study were all employees, totaling 213 people and the samples taken in this study were 83 people. The validity test has a value of 17 questions, all of which have a value greater than 0.2159 or rcount > rtable, which means that it can be concluded that all questions are valid. The reliability test obtained a Cronbach's alpha value of 0.731 and this value was greater than 0.60 or 0.731 > 0.60 so that the questionnaire used could be declared reliable. Partially the variable Repressive Supervision (X4) has a partial effect on Employee Performance (Y) tcount > ttable (4.574 > 1.99085) and the variables of Internal Control (X1), External Monitoring (X2), Preventive Control (X3) have no partial effect on Employee Performance (Y) tcount < ttable Internal Monitoring (X1) (0.221 < 1.99085), External Monitoring (X2) (1.044 < 1.99085), Preventive Monitoring (X3) (0.145 < 1.99085) . Because the tcount results of Repressive Supervision (X4) are greater than tcounts of Internal Supervision (X1), External Supervision (X2), and Preventive Supervision (X3), Repressive Supervision (X4) is declared to have a dominant influence on Employee Performance (Y).